2018
DOI: 10.1097/md.0000000000009893
|View full text |Cite
|
Sign up to set email alerts
|

A traumatic hepatic artery pseudoaneurysm and arterioportal fistula, with severe diarrhea as the first symptom

Abstract: Rationale:Hepaticarterioportal fistula (APF) is a rare cause of portal hypertension and gastrointestinal hemorrhage, and presents as abnormal communication between the hepatic artery and portal vein. Percutaneous liver biopsy is a main iatrogenic cause of AFP. However, non-iatrogenic, abdominal, trauma-related APF is rarely reported.Patient concerns:A 29-year-old man presenting with severe, watery diarrhea was transferred to our hospital, and his condition was suspected to be acute gastroenteritis because he a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Traumatic cause for an APF is mostly related to surgical interventions or liver biopsy. Non-iatrogenic abdominal trauma that is related to APF is rarely reported 4. In our case the patient had history of blunt trauma to the abdomen which resulted in avulsion of common hepatic artery bifurcation with development of pseudoaneurysm and high-flow APF.…”
Section: Discussionmentioning
confidence: 75%
“…Traumatic cause for an APF is mostly related to surgical interventions or liver biopsy. Non-iatrogenic abdominal trauma that is related to APF is rarely reported 4. In our case the patient had history of blunt trauma to the abdomen which resulted in avulsion of common hepatic artery bifurcation with development of pseudoaneurysm and high-flow APF.…”
Section: Discussionmentioning
confidence: 75%
“…Nevertheless, the results described present functional solutions for selected cases, with low morbidity and mortality. 1,4,7,10,20 It can be concluded that for this case of renal-splanchnic fistula with high output and outflow via large caliber veins causing severe PH, endovascular deployment of an oversized vascular occlusion plug proved to be an effective treatment, resulting in significant clinical improvement of the patient.…”
Section: Discussionmentioning
confidence: 89%
“…4,7 Blood flow and fistula diameter are very important to choosing a device that will achieve adequate closure of the communication without embolization of non-target vessels. 4,10 Small APFs and those with low blood flow can be adequately treated with embolization agents or sclerosants, whereas APFs will require occlusion devices that are oversized to avoid migration. 4 Arterial embolization is very effective for treatment of APFs with a single communication, and steel coils, ethanol, embolizing polymer particles, isobutyl cyanoacrylate glue, detachable balloons, occluding devices (vascular plugs), and angioplasty balloons are all used.…”
Section: Discussionmentioning
confidence: 99%
“…In AHVFs, altered liver parameters and features of right heart failure can be seen. 12 Contrarily in an APF, GI bleed can be the presentation as portal hypertension will be present. Clinically if shunts are significant, a holosystolic murmur can be heard.…”
Section: Discussionmentioning
confidence: 99%
“…4 Diverse modalities are present to diagnose arterio-venous fistulas, which include screening tools like doppler ultrasound, contrast-enhanced CT, MR angiography, and DSA. 12 Currently, the gold standard armamentarium in diagnosing, managing and follow-up is DSA with the advantage of providing us with meticulous details regarding the site of fistula and the flow details and simultaneously performing endovascular interventions. 14 The management options are embolization with particle agents like polyvinyl acrylate and gel foam, liquid agents like onyx and glue, mechanical agents like stainless steel coils, and balloons, 5,15 which can be used alone or in combination.…”
Section: Discussionmentioning
confidence: 99%